Noncontact measurement of charge carrier lifetime and mobility in GaN nanowires. - Parkinson, P; Dodson, C; Joyce, H; Bertness, K; Sanford, N; Herz, L; Johnston, M (2012)
The first noncontact photoconductivity measurements of gallium nitride nanowires (NWs) are presented, revealing a high crystallographic and optoelectronic quality achieved by use of catalyst-free molecular beam epitaxy. In comparison with bulk material, the NWs exhibit a long conductivity lifetime (>2 ns) and a high mobility (820 ± 120 cm(2)/(V s)). This is due to the weak influence of surface traps with respect to other III-V semiconducting NWs and to the favorable crystalline structure of the NWs achieved via strain-relieved growth.